2016
DOI: 10.4067/s0718-52862016000200005
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of visa restrictions on international tourist flows using panel data: Un análisis con datos de panel

Abstract: Using newly panel data on visa restrictions for the years 2000 and 2010 in a theory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
1
12
2
Order By: Relevance
“…9 Another study, using a theory grounded gravity model, determined a causal negative impact of visa restrictions on international tourist flows. 10 Yet another study estimates that, on average, the introduction of a visa requirement reduces direct bilateral flows by between 41 and 47 per cent, while increasing the flows towards other destinations between 3 and 14 per cent. 11 Mathias Czaika and Hein de Haas have found that visa introduction causes an asymmetric policy effect.…”
Section: Eric Neumayer Suggests That Visamentioning
confidence: 98%
“…9 Another study, using a theory grounded gravity model, determined a causal negative impact of visa restrictions on international tourist flows. 10 Yet another study estimates that, on average, the introduction of a visa requirement reduces direct bilateral flows by between 41 and 47 per cent, while increasing the flows towards other destinations between 3 and 14 per cent. 11 Mathias Czaika and Hein de Haas have found that visa introduction causes an asymmetric policy effect.…”
Section: Eric Neumayer Suggests That Visamentioning
confidence: 98%
“…Several factors influence traveling, such as distance (Artal-Tur, Pallardó-López, & Requena-Silvente, 2016;Mariyono, 2017;Mishra & Bansal, 2017), cost (Moon & Han, 2019;Chhorn, 2017;Utama, 2016), assessment over the destination (Battour, Hakimian, Ismail, & Boğan, 2018;Liu, Li, & Kim, 2017), infrastructure support, availability…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the factors that motivate tourists to visit a destination, there are also several external factors, such as destination marketing (Liu, Pan, & Zheng, 2019;Sukirman, 2017) and policies issued by the destination countries (Artal-Tur et al, 2016;Mylonopoulos, Moira, & Kikilia, 2016;Ob & Mp, 2018). Data from Badan Pusat Statistik (2020) mentioned that foreign tourists in 2019 reached 16.106.954 international arrivals.…”
Section: Introductionmentioning
confidence: 99%
“…This time, visa fees for Chinese visitors are continuously under review. Admittedly, visas are an important instrument that governments use to control who can enter their countries for specific purposes (Artal-Tur et al, 2016). The immediate effect of such an instrument is to ensure security for a country where undesirable foreign nationals are screened and prevented from entering.…”
Section: Introductionmentioning
confidence: 99%